2021
DOI: 10.3390/ijms22115770
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Based Therapeutics for Atherosclerosis and Cardiovascular Diseases

Abstract: Cardiovascular disease is the leading cause of death worldwide, and its prevalence is increasing due to the aging of societies. Atherosclerosis, a type of chronic inflammatory disease that occurs in arteries, is considered to be the main cause of cardiovascular diseases such as ischemic heart disease or stroke. In addition, the inflammatory response caused by atherosclerosis confers a significant effect on chronic inflammatory diseases such as psoriasis and rheumatic arthritis. Here, we review the mechanism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 140 publications
0
22
0
Order By: Relevance
“…Conversely, for the detection of antibodies for other purposes (e.g. to monitor immunotherapy), the concentration level of the target antibody can be much higher (high nM low uM range) (Robert et al, 2001;Ji and Lee, 2021;Chames et al, 2009). Thus, the C HalfMax values we achieved here (Figure 4B) show sensitive concentration ranges relevant for diagnostic applications.…”
Section: Discussionmentioning
confidence: 85%
“…Conversely, for the detection of antibodies for other purposes (e.g. to monitor immunotherapy), the concentration level of the target antibody can be much higher (high nM low uM range) (Robert et al, 2001;Ji and Lee, 2021;Chames et al, 2009). Thus, the C HalfMax values we achieved here (Figure 4B) show sensitive concentration ranges relevant for diagnostic applications.…”
Section: Discussionmentioning
confidence: 85%
“…An expert committee published the National Cholesterol Education Program in United States, emphasizing that low density lipoprotein (LDL) should be the primary target of cholesterol-lowering therapy in atherosclerosis ( Tavares et al, 2021 ). In particular, clinical trials have demonstrated that lowering LDL levels can reduce the risk of atherosclerosis ( Ference et al, 2017 ; Ji and Lee, 2021 ). Notably, the increased lipid in the serum and liver was reduced with the administration of berberine, which improved intima-media thickening, restored aortic endothelium-dependent vasodilatation, and alleviated atherosclerotic lesions in APOE (−/−) mice fed a western-type diet for 12 weeks ( Tan et al, 2020 ).…”
Section: Effects Of Berberine On Vascular Diseasesmentioning
confidence: 99%
“…However, due to their high price, they remain underutilized and difficult to prescribe in clinical practice [ 206 ]. Antibodies that neutralize inflammatory cytokines (TNF- α , IL-1β, IL-6, IL-17, and IL-12/23) have shown promising but contradictory results and thus warrant further research [ 207 , 208 ]. Monoclonal antibodies against PCSK9 (alirocumab, evolocumab) were also developed and studied in large clinical programs.…”
Section: Established and Emerging Therapeutical Strategies For Atherosclerosismentioning
confidence: 99%